Leisure life : myth, masculinity and modernity - Blackshaw, Tony, 1960- (Routledge, 2003)
Leisure Life awakens the sociological imagination. It offers a new approach to the study of masculinity and the ethnography of leisure, making it appropriate for courses in sociology, leisure, cultural and gender studies.